1993
DOI: 10.1111/j.1469-8986.1993.tb02085.x
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude and bilateral coherency of facial and jaw‐elevator EMG activity as an index of effort during a two‐choice serial reaction task

Abstract: In earlier studies, positive but inconsistent relationships have been reported between mental effort and electromyogram (EMG) amplitude in task-irrelevant limb muscles. In this study, we explored whether facial EMG activity would provide more consistent results. Tonic EMG activity of six different facial and jaw-elevator muscles was bilaterally recorded during a two-choice serial reaction task with paced presentation of auditory or visual signals. In Experiment 1, task load (signal presentation rate) was kept … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(101 citation statements)
references
References 69 publications
4
96
1
Order By: Relevance
“…This finding is consistent with previous findings of higher EMG 536 amplitude in the lower lip during speech and inner speech (e.g., Barlow & Netsell, 1986 However, although a functional distinction can be drawn between the forehead and the lip 546 muscles, one should acknowledge the fact that these two sets of muscles can be commonly 547 activated during some behaviours. For instance, Van Boxtel & Jessurun (1993) have shown that 548 orbicularis oris inferior and frontalis were both activated during a two-choice serial reaction task 549 in which nonverbal auditory or visual signals were presented. Moreover, there was a gradual 550 increase in EMG activity in these muscles during the task, either when the task was prolonged or 551 when the task was made more difficult.…”
Section: 1experiments 1 510mentioning
confidence: 99%
“…This finding is consistent with previous findings of higher EMG 536 amplitude in the lower lip during speech and inner speech (e.g., Barlow & Netsell, 1986 However, although a functional distinction can be drawn between the forehead and the lip 546 muscles, one should acknowledge the fact that these two sets of muscles can be commonly 547 activated during some behaviours. For instance, Van Boxtel & Jessurun (1993) have shown that 548 orbicularis oris inferior and frontalis were both activated during a two-choice serial reaction task 549 in which nonverbal auditory or visual signals were presented. Moreover, there was a gradual 550 increase in EMG activity in these muscles during the task, either when the task was prolonged or 551 when the task was made more difficult.…”
Section: 1experiments 1 510mentioning
confidence: 99%
“…As such, activation of the corrugator muscle putatively reflects the bipolar valence dimension (positive-negative) that is central to core affect (Larsen, Norris, & Cacioppo, 2003). Although consistent with the negative valence of conflict, alternate accounts propose that the corrugator muscle tracks cognitive demand (de Morree & Marcora, 2010;van Boxtel & Jessurun, 1993). Therefore, because conflict is tightly coupled with effort, error-related corrugator engagement might reflect demand, rather than affect.…”
Section: Peripheral Nervous System Arousal To Conflictmentioning
confidence: 99%
“…For instance, Van Boxtel & Jessurun (1993) have shown that 545 orbicularis oris inferior and frontalis were both activated during a two-choice serial reaction task 546 in which nonverbal auditory or visual signals were presented. Moreover, there was a gradual 547 increase in EMG activity in these muscles during the task, either when the task was prolonged or 548 when the task was made more difficult.…”
Section: 1experiments 1 507mentioning
confidence: 99%